Thyroid hormone status in preeclampsia patients: A case-control study - Nineetha Muraleedharan; Jessy Sumangala Janardhanan (Wolters Kluwer Medknow Publications, 2017)
Context: Preeclampsia (PE) is a common complication of pregnancy associated with high morbidity. Antiangiogenic factors are raised in PE, which may affect thyroid secretion. Aims: The aim of this study was to determine the association between thyroid hormonal status in PE and the severity of PE and also any correlation between albumin levels and thyroid status. Materials and Methods: Cases include forty women between 30 and 38 weeks of gestation with PE. Forty healthy normotensive pregnant women in third trimester constituted the control group. Thyroid profile (free triiodothyronine [FT3], triiodothyronine [T3], free thyroxine [FT4], thyroxine [T4], and thyroid stimulating hormone [TSH]) was measured by enzyme-linked immunosorbent assay technique. Analysis and Results: Mean, median, standard deviation for quantitative variables were compared by Student's t-test. Percentage values were compared using Chi-square test. ANOVA tests and post hoc analysis were done. Odds ratio was used to assess risk for hypothyroidism. TSH was significantly high in PE (3.76 ± 1.55) than controls (2.30 ± 0.94 mIU/L). Mean FT3 in PE was 2.12 ± 0.55 and in controls was 2.43 ± 0.47 pg/ml. FT4 in cases was 1.16 ± 0.24 and in controls was 1.33 ± 0.27 ng/dL, suggestive of hypothyroidism. The mean serum albumin was significantly lesser (3.11 ± 0.39 g/dL) in PE. Conclusion: Preeclamptics had 11 times, severe preeclamptics 31.5 times while mild preeclamptics had five times more risk for hypothyroidism. Risks for hypothyroidism increase with the severity of PE.